Comparing Genotype-guided, Platelet-function–guided, Universal Potent, And Universal Clopidogrel Antiplatelet Therapy Strategies Post-PCI: A Systematic Review And Network Meta-analysis - Eleeas, Abraham Tory; Athaseno, Aryagani Manggala; Tambunan, Alphatar Magnus Jonathan (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Optimal P2Y12 inhibitor selection after percutaneous coronary intervention (PCI) is pivotal, yet high-quality evidence remains limited, creating uncertainty for routine practice. This paper synthesizes evidence comparing four post-PCI antiplatelet therapy strategies: genotype-guided (CYP2C19-directed), platelet-function-guided, universal potent P2Y12 inhibition, and universal clopidogrel. Comprehensive searches of three databases were conducted to identify eligible randomized controlled trials. Study quality was appraised using Cochrane RoB 2.0, while evidence certainty was assessed with the GRADE framework. A frequentist NMA was performed using a random-effects model. Interventions were compared using risk ratios (RRs) with 95% confidence intervals (CIs) for binary clinical outcomes (major adverse cardiovascular events, bleeding, and stent thrombosis) and mean differences (MDs) with 95% CIs for the continuous pharmacodynamic outcome of platelet reactivity. Cost outcomes, when reported, were synthesized narratively. The comparative performance of each intervention was summarized and ranked using the Surface Under the Cumulative Ranking Curve (SUCRA). Findings revealed a distinct hierarchy among antiplatelet therapy strategies. The universal potent P2Y12 inhibitor strategy consistently ranked highest for preventing ischemic events but was associated with a significantly increased risk of major bleeding. Conversely, the universal clopidogrel strategy demonstrated the most favorable safety profile for bleeding but the lowest ischemic efficacy. This analysis confirms that while universal potent and clopidogrel strategies represent extreme ends of the efficacy-safety spectrum, guided strategies bridge the gap by delivering the ischemic protection of potent therapy while reducing the risk of bleeding, demonstrating superior clinical benefit. Keywords: CYP2C19, Genotype-Guided Therapy, P2Y12 Inhibitors, Percutaneous Coronary Intervention, Platelet Function Testing